1976
DOI: 10.1136/oem.33.4.217
|View full text |Cite
|
Sign up to set email alerts
|

The biology of talc.

Abstract: -229. The biology of talc. Data are presented on the effects on health of talc dusts from exposure in industry and use of talc-containing health products. The mineralogy of talc and the composition of cosmetic and industrial grade talc dusts are described. Studies in animals are reviewed, and epidemiological data are considered in relation to exposures that occur during industrial and consumer uses of talc dusts. Hamsters exposed to 8 mg/m3 of respirable cosmetic grade talc dust for up to 150 minutes a day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 69 publications
(96 reference statements)
1
36
0
Order By: Relevance
“…These data and those obtained in other animal studies have failed to produce any evidence that cosmetic talc is a carcinogen (Hildick-Smith, 1976a).…”
Section: Letter To the Editormentioning
confidence: 85%
See 3 more Smart Citations
“…These data and those obtained in other animal studies have failed to produce any evidence that cosmetic talc is a carcinogen (Hildick-Smith, 1976a).…”
Section: Letter To the Editormentioning
confidence: 85%
“…Prospective and retrospective epidemiological studies of employees milling and mining cosmetic grade talc have shown no difference in the incidence of pulmonary fibrotic disease or cancer between the mine employees and a control unexposed cohort, even where a group of talc millers was exposed to approximately 7,800 times as much talc dust in 1 wk as a consumer would be exposed to in 1 wk (Hildick-Smith, 1976a, 1976b.…”
Section: Letter To the Editormentioning
confidence: 98%
See 2 more Smart Citations
“…It is doubtful whether the products tested always consisted mainly of the mineral talc. The earliest report of a case of talc pneumoconiosis is from the year 1896 [16,17]. Since then talcosis has become established as a diffuse pulmonary fibrosis, similar to asbestosis and frequently with thickening of the pleura.…”
Section: Effects In Manmentioning
confidence: 99%